Angiotensin‐converting enzyme inhibitors increase anti‐fibrotic biomarkers in African Americans with left ventricular hypertrophy - Romero, Cesar; Mathew, Shobi; Wasinski, Benjamin; Reed, Brian; Brody, Aaron; Dawood, Rachelle; Twiner, Michael J.; McNaughton, Candace D.; Fridman, Rafael; Flack, John M.; Carretero, Oscar A.; Levy, Phillip D. (The journal of clinical hypertension (Greenwich, Conn.), 2021)
Angiotensin‐converting enzyme inhibitors (ACEi) are part of the indicated treatment in hypertensive African Americans. ACEi have blood pressure‐independent effects that may make them preferred for certain patients. We aimed to evaluate the impact of ACEi on anti‐fibrotic biomarkers in African American hypertensive patients with left ventricular hypertrophy (LVH). We conducted a post hoc analysis of a randomized controlled trial in which hypertensive African American patients with LVH and vitamin D deficiency were randomized to receive intensive antihypertensive therapy plus vitamin D supplementation or placebo. We selected patients who had detectable lisinopril (lisinopril group) in plasma using liquid‐chromatography/mass spectrometry analysis and compared them to subjects who did not (comparison group) at the one‐year follow‐up. The pro‐fibrotic marker type 1 procollagen C‐terminal propeptide (PICP) and the anti‐fibrotic markers matrix metalloproteinase‐1 (MMP‐1), tissue inhibitor of metalloproteinases 1 (TIMP‐1), telopeptide of collagen type I (CITP), and N‐acetyl‐seryl‐aspartyl‐lysyl‐proline (Ac‐SDKP) peptide were measured. Sixty‐six patients were included, and the mean age was 46.2 ± 8 years. No difference was observed in the number and intensity of antihypertensive medications prescribed in each group. Patients with detectable lisinopril had lower blood pressure than those in the comparison group. The anti‐fibrotic markers Ac‐SDKP, MMP‐1, and MMP‐1/TIMP‐1 ratio were higher in patients with detectable ACEi (all p < .05). In a model adjusted for systolic blood pressure, MMP‐1/TIMP‐1 (p = .02) and Ac‐SDKP (p < .001) levels were associated with lisinopril. We conclude that ACEi increase anti‐fibrotic biomarkers in hypertensive African Americans with LVH, suggesting that they may offer added benefit over other agents in such patients.